Peasants Making History. Living in an English Region 1200–1540 - Stamper, Paul (Medieval Settlement Research, 2023)
Drawing on his half-century of fieldwork and documentary research on the west midlands, Chris Dyer here delivers a data-rich, yet intimate picture of peasant life and society over some 400 years. His region is Warwickshire, Worcestershire and Gloucestershire (the home territory of Piers Plowman), the contrasting landscape divisions of which – Arden, Felden, the Cotswolds, the Vale of Gloucester and the Forest of Dean – allow investigation of local character and variation in economy, society and settlement types. Those familiar with Dyer’s earlier work will not be surprised to find that a central theme is that many peasants had a better life, and both individually and as communities exerted greater control over their lives, than was long thought.